Time-dependent reliability assessment of corroded metal structures based on Physics of Failure (PoF): With a case study of cast iron pipe. (November 2022) - Mulenga, Kabwe; Wang, Weigang; Li, Chun-Qing; Xie, Min
Abstract: In most metal structures, corrosion has been recognized as the main cause of failure, and fracture often occurs in structures subjected to corrosion, e.g., metal pipes. Since the evolution of a corrosion defect into a crack takes the majority of a structure's lifespan, accurate quantification of this transition limit state is significant in assessing the probability of failure. This paper aims to propose a methodology for predicting the occurrence of a crack in corroded structures based on the Physics-of-Failure (PoF) theory. The Stress Intensity Factor (SIF) concept and the J-integral-based finite element analysis are used to derive the solution of the SIFs in the corroded structure. A cast iron pipe with a crack-shape corrosion defect is taken as an example. A model for estimating the SIF for a corrosion pit with high aspect ratio has been proposed. The evolution of SIF is modeled by a stochastic process, and an advanced time-dependent method (i.e., upcrossing method) is used to quantify the probability of failure. It is found that combining the concept of Physics-of-Failure with time-dependent reliability method can provide an effective tool for predicting the failure probability of corroded structures. It is also found from the sensitivity analysis that the internal pressure has the highest effect on the probability of failure, followed by the corrosion pit depth. The results from this paper offer a necessary basis for safety and reliability analysis of corroded metal pipes, providing asset managers a cost-effective tool in planning maintenance works.